Public History of Chinese-Javanese Harmony in Yogyakarta for History Learning with Diversity Insights - Kurniawan, Hendra; Supriatna, Nana; Mulyana, Agus; Yulifar, Leli (Paramita: Historical Studies Journal, 2023)
History learning is often still dominated by mainstream material in textbooks. Local historical studies, such as Chinese-Javanese relations in Yogyakarta, have yet to be accommodated. For this reason, this study formulates the construction of history learning about Chinese-Javanese harmony in Yogyakarta in the context of utilizing public history. This qualitative research uses library methods to identify history learning sources about Chinese-Javanese relations in Yogyakarta. Furthermore, with the critical theory paradigm, the construction of history learning with the perspective of diversity regarding Chinese-Javanese harmony in Yogyakarta is formulated that can be applied in the classroom. As a result, it was found that the existence of the Chinatown area, inscriptions at the Yogyakarta Palace, kelenteng (temples), wayang Cina-Jawa or Wacinwa (Chinese-Javanese puppets), and local cuisine can be a source of learning the history of Chinese-Javanese harmony in Yogyakarta. These learning sources have the potential to be studied in the space of public history, so history learning can be constructed by encouraging students to produce public historical works in digital form through social media so that they can be widely enjoyed. Constructing history learning like this can contribute to building diverse discourses in society to strengthen national integration.Keywords: Chinese, Yogyakarta, public history, history learning, diversity.Pembelajaran sejarah kerap masih didominasi materi arus utama dalam buku teks. Kajian sejarah lokal seperti relasi Tionghoa-Jawa di Yogyakarta belum terakomodasi. Untuk itu, penelitian ini merumuskan konstruksi pembelajaran sejarah tentang keharmonisan Tionghoa-Jawa di Yogyakarta dalam konteks pemanfaatan sejarah publik. Penelitian kualitatif ini menggunakan metode penelitian kepustakaan untuk mengindentifikasi sumber-sumber belajar sejarah tentang relasi Tionghoa-Jawa di Yogyakarta. Selanjutnya dengan paradigma teori kritis dirumuskan konstruksi pembelajaran sejarah berwawasan kebinekaan mengenai keharmonisan Tionghoa-Jawa di Yogyakarta yang dapat diterapkan di kelas. Hasilnya didapati bahwa keberadaan kawasan Pecinan, prasasti-prasasti di Keraton Yogyakarta, kelenteng, wayang Cina Jawa (Wacinwa), dan kuliner lokal dapat menjadi sumber belajar sejarah keharmonisan Tionghoa-Jawa di Yogyakarta. Sumber-sumber belajar tersebut berpotensi untuk dikaji dalam ruang sejarah publik, maka pembelajaran sejarah dapat dikonstruksi dengan mendorong siswa menghasilkan karya sejarah publik dalam bentuk digital melalui media sosial sehingga dapat dinikmati secara luas. Konstruksi pembelajaran sejarah seperti ini dapat berkontribusi membangun wacana kebinekaan di tengah masyarakat untuk menguatkan integrasi bangsa.Kata kunci: Tionghoa, Yogyakarta, sejarah publik, pembelajaran sejarah, kebinekaan.